Thermoregulation : from basic neuroscience to clinical neurology. - Romanovsky, Andrej A. (Handbook of clinical neurology ;, 2018)
"Thermoregulation, Part II: From Basic Neuroscience to Clinical Neurology, Volume 155, not only reviews how body temperature regulation changes in neurological diseases, but also how this aspect affects the course and outcomes of each disease. Other sections of the volume review three therapeutic approaches that are aimed at manipulating body temperature, including induced hypothermia, induced hyperthermia and antipyretic therapy. The book is comprised of nine sections across two volumes, five dealing with the basic aspects of body temperature regulation and four dealing with the clinical aspects. Basic sections cover the Thermoregulation system, Thermoreceptors, Thermoeffectors, Neural pathways, and Thermoregulation as a homeostatic function. In addition, the book covers the physiology and neuroanatomy of the thermoregulation system and provides descriptions of how the regulation of body temperature intervenes with other physiological functions (such as sleep, osmoregulation, and immunity), stress, exercise and aging. Basic sections serve as an introduction to the four clinical sections: Body Temperature, Clinical Significance, Abnormal Body Temperature, Thermoregulation in Neurological Disease and Therapeutic Interventions. Presents a clear, logical pathway from the fundamental physiology of thermoregulation, through neurobiology, to clinical applications and diseaseEnables researchers and clinicians to better understand the value of temperature measurement in disease and the use of temperature as a therapy Integrates content from a broad field of research, including topics on the molecular physiology of temperature receptors, to the management of accidental hypothermia"--Publisher's description